O saber impotente: estudo da noção de ciência na obra infantil de Monteiro Lobato - Camenietzki, Carlos Ziller (1988)
The children’s books of Monteiro Lobato present Science in three phases. In the first, Science is useless and represents an obstacle to the unfolding of the adventures. In the second, it is the very power which drives the stories. In the third, it is seen as a tool which is misused by civilization. Monteiro Lobato joined a group of intellectuals from São Paulo who were involved in the formation of the Democratic party of the twenties. The structure of the phases identified in the children's books corresponds to the political direction followed by the group. At first, it struggles to assert itself, to establish itself in regional politics against the conservatism of the PRP. In the second period it is victorious, governing the state, and finally it is defeated by the coup of 1937, and is disbanded. Its members are co-opted or persecuted. In this way, the children's books of Lobato portray the saga of oligarchic liberalism in São Paulo during the First Republic.